Risk-Based Disease Management in the Fight Against to Bovine Tuberculosis; Area Prioritization - B, Şentürk (Journal of Diseases, 2016)
In this study, regional distribution of bovine tuberculosis disease in Turkey over a period of 10 years was investigated using Office International des Epizooties data. The number of outbreaks of the geographical regions put together in Microsoft Excel programme. Descriptive statistics and Correlation analysis was used in the study. Six disease-specific evaluation criteria were determined to explain the disease factors. In Turkey, the number of outbreaks (r=0.693; p=0.000<0.01) was found to be significant. But the relationship of the number of outbreaks of the disease with the number of animals per km2 (animal density) was found to be (-.016) insignificant (P>0.05). The rusults of present study to demostrate that epidemiologic data analysis was first implemented to disease management programme. Thus if the risk area determined, cost of controlling of the disease programme will be reduced and effective contol programme must be implemented to the high risk area. This study recomended that the disease outbreaks management will be planned firstly high risk areas with a risk based disease managemnet plan. This approch will be decreased the disease outbreaks and the public cost of the disease will be reduced in near future.